No news, no excitement, no creativity: Moderating roles of adaptive humour and proactivity - De Clercq, D. (2021)
When employees believe that organizational authorities are engaged in unfair information provision, it might evoke some negative behavioural responses, like diminished creativity. But when and why are such responses more likely? To answer these questions, the current study investigates the mediating role of job dissatisfaction in the relationship between unfair organizational information provision and creative behaviour, as well as the moderating roles of employees' own adaptive humour and proactivity. Survey data, collected from employees who operate in the oil and gas sector, reveal that employees' convictions that organizational leaders are not open in their communication can prompt them to avoid creative work activities, because these employees become unhappy with their jobs. This mediating role of job dissatisfaction is less salient if they have a good sense of humour and like to take initiative though. Organizations therefore should take these findings as a relevant caution: Lack of excitement about their jobs, as informed by organizational information deficiencies, can make employees complacent. To address this potentially negative outcome, organizations might help employees leverage their own valuable personal resources